Liposomes for brain delivery. (July 2013) - Lai, Francesco; Fadda, Anna Maria; Sinico, Chiara
<x xml:space="preserve">Abstract</x> Introduction: Development of drug delivery systems for brain delivery is one of the most challenging research topics in pharmaceutical areas, mainly due to the presence of the blood–brain barrier (BBB), which separates the blood from the cerebral parenchyma thus limiting the brain uptake of the majority of therapeutic agents. Among the several carriers, which have been studied to overcome this problem, liposomes have gained increasing attention as promising strategies for brain-targeted drug delivery. The most advantageous features of liposomes are their ability to incorporate and deliver large amounts of drug and the possibility to decorate their surface with different ligands. Areas covered: The purpose of this review is to explore the different approaches studied to transport and deliver therapeutics and imaging agents to the brain by using liposomes. In the first part of the review, particular attention is paid to describe the anatomy of the BBB and different physiological transport mechanisms available for drug permeation. In the second part, the different strategies for the delivery of a drug to the brain using liposomes are reviewed for each transport mechanism. Expert opinion: Over the last decade, there have been significant developments concerning liposomal brain delivery systems conjugated with selected ligands with high specificity and low immunogenicity. An universally useful liposomal formulation for brain targeting does not exist but liposome design must be modulated by the appropriate choice of the specific homing device and transport mechanism.